The Effect of Using the Cognitive Strategies on the Achievement and Practical Performance of Physiology (Modeling / Reciprocal teaching) (Medico Legal Update, 2020)
The research aims to know the impact of using the strategies of cognitive perception on the achievement andpractical performance of physiology, and to achieve the goal of the research under the formulation of zerohypotheses: There is no statistically significant difference at the level of (05.0) between the average grades ofstudents in the achievement of students of the three groups of physiology. There is no statistically significantdifference at the level of (05.0) between the average grades of students in the practical performance of thestudents of the three groups of physiology. The research community consisted of the students of the firststage in the Technical Institute. The sample was randomly tested as it reached 45 students. The equivalencebetween the research groups was confirmed through the following variables: (Age, Intelligence). As forpractical achievement, (15) objective test items were drafted covering the subject, and to ensure the validityof the test was presented to a number of experts specialized in education and teaching methods, and thevalidity and consistency of the discrimination factor and the difficulty factor and the effectiveness ofalternatives to the test were calculated.